Characterisation of the Flavour and the Chemical Composition of Lager Beer after Ageing in Varying Conditions - Saison, Daan; Vanbeneden, Nele; De Schutter, David P.; Daenen, Luk; Mertens, Tom; Delvaux, Filip; Delvaux, Freddy R. (BrewingScience, 2010)
Aged beer flavour was studied by ageing a lager beer in different conditions (varying temperature-time profiles, different oxidative conditions and varying pH and ethanol concentrations). This led to beers with a varying aged flavour, which could be explained by differences in the reaction rate of ageing reactions. High temperatures, oxidative conditions and to a lesser extent, a lower pH, accelerated beer ageing. Enhanced (E)-2-nonenal formation probably led to the greater perception of cardboard flavour after ageing at high temperatures. Madeira flavour was only perceived after ageing at 20 °C and ribes flavour was mainly perceived in oxidatively aged beer. In beers with these flavour notes, high concentrations of acetal-dehyde, Strecker aldehydes and diacetyl were found and in the Madeira flavoured beer, also of 2-furfuryl ethyl ether and 5-hydroxymethylfurfural. In the end, this study provides an overview of the different aged flavours that can develop in different ageing conditions and the corresponding flavour compounds that make up the chemical composition of these flavours.